2022
DOI: 10.1002/jev2.12260
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the extracellular vesicle surface for clinical molecular biology

Abstract: Extracellular vesicles (EVs) are lipid‐membrane enclosed nanoparticles that play significant roles in health and disease. EVs are abundant in body fluids and carry an array of molecules (proteins, lipids, nucleic acids and glycans) that reflect the identity and activity of their cell‐of‐origin. While the advent of high throughput omics technologies has allowed in‐depth characterisation of EV compositions, how these molecular species are spatially distributed within EV structures is not well appreciated. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 246 publications
(447 reference statements)
0
37
0
Order By: Relevance
“…Shelke et al (69) reported that TGF-β1 bound to EVs gives longer cell signaling over time compared to freely circulating TGF-β1. The present study demonstrated that a substantial part of the three TGF-β isoforms present in SP were bound to sEVs either as cargo inside, or outside in the so-called molecular corona surrounding the EVs (70), which plays a key role in the functional spectrum of EVs (71). Similar results were achieved by Fitzgerald et al (72) who reported that a substantial portion of several cytokines circulating in human blood plasma and amniotic fluid, TGF-βs among them, were bound to EVs, either inside or outside.…”
Section: Discussionmentioning
confidence: 65%
“…Shelke et al (69) reported that TGF-β1 bound to EVs gives longer cell signaling over time compared to freely circulating TGF-β1. The present study demonstrated that a substantial part of the three TGF-β isoforms present in SP were bound to sEVs either as cargo inside, or outside in the so-called molecular corona surrounding the EVs (70), which plays a key role in the functional spectrum of EVs (71). Similar results were achieved by Fitzgerald et al (72) who reported that a substantial portion of several cytokines circulating in human blood plasma and amniotic fluid, TGF-βs among them, were bound to EVs, either inside or outside.…”
Section: Discussionmentioning
confidence: 65%
“…The EVs membrane is a highly interactive and dynamic surface area that is responsible for facilitating EVs interactions with the extracellular environment [ 59 ]. It has been suggested that the interactions of small EVs act as modulators of signaling in biological processes, such as metastasis, cancer regulation, and tissue regeneration [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the interactions of small EVs act as modulators of signaling in biological processes, such as metastasis, cancer regulation, and tissue regeneration [ 60 ]. Some of the mechanisms proposed to understand the interaction of EVs with other tissues are as follows: (1) fusion of the plasma membrane of EVs with the target cell, releasing its content inside; (2) vehicles of proteins and cellular components; upon arrival to the target cell, they can be fragmented by the action of proteases and act as a ligand for target cell receptors; and (3) endocytosis and pinocytosis [ 59 , 61 ]. Our results showed that the Zeta potential of EVs had several significant associations with clinical characteristics of the patients, as well as weight and visceral fat.…”
Section: Discussionmentioning
confidence: 99%
“…EV-based DDS present multiple advantages ( Figure 2 ): (1) their structure is composed of an aqueous core and a rich lipid bilayer surface structure, allowing for the compartmentalization and solubilization of both hydrophilic and lipophilic agents [ 59 ]. (2) EVs carry various biomolecules, such as proteins, lipids, and DNA and RNA species, depending on the producer cell types; the surface structure consists of fatty acids, high concentrations of cholesterol, sphingomyelin, ceramides, and other lipids; and interestingly, this surface also contains proteins that are implicated in adhesion, such as tetraspanins and αβ integrins, conferring on EVs an endogenous homing and targeting capacity [ 60 ]. (3) EVs are considered to be non-immunogenic, with a lower risk of allogeneic immune rejection from the host [ 61 ].…”
Section: Mesenchymal Stromal Cell-derived Extracellular Vesicles (Msc...mentioning
confidence: 99%